Evaluating the implementation of an emotional wellbeing programme for primary school children using participatory approaches. (September 2015) - Clarke, Aleisha M; Sixsmith, Jane; Barry, Margaret M
Objective: This paper reports on the use of child participatory approaches to evaluate the implementation and impact of the Zippy's Friends emotional wellbeing programme on children in disadvantaged primary schools in Ireland. Design: As part of the overall evaluation study, which comprised a clustered randomised controlled trial, qualitative participatory approaches were utilised to explore children's experiences of the Zippy's Friends programme. Setting: From the overall sample of 44 primary schools ( N = 717 pupils) that participated in the evaluation study, a subsample of 9 classes ( n = 161 children) from the intervention and control groups was randomly selected to take part in child participatory workshops at pre-intervention, interim and post-intervention. Method: A semi-structured child participatory workshop consisting of three activities, including draw and write technique, feelings activity and group brainstorming, was used to explore the children's experiences of the programme and its impact on their coping strategies and emotional literacy skills. Results: The results from the draw and write activity provided evidence of the positive impact of the programme on children's use of problem-solving and support-seeking strategies in coping with certain problem situations. Findings from the participatory workshop also helped provide insight into how the programme impacted on children's emotional literacy skills. Children in the intervention group had a broader range of vocabulary and understanding in relation to emotions concerning problem situations. In addition, children identified factors that, from their perspective, supported their engagement with the programme, including the use of narrative through story and the activity-based nature of the programme. Conclusion: The use of participatory approaches generated data that enriched our understanding of how children experienced and benefited from the programme from their own perspective, thereby providing insights that were untapped by other research methods in this study.